Right to work of displaced women of Facatativá - Vega-Vaca, Ángela Consuelo (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The problem of the forced displacement in Colombia has taken importance over time due to the different struggles of their direct actors. Especially for women who have the direct responsibility for the economic and emotional support of their families at the time of life at which displacement takes place. Within these strategies they initially go to the State to get urgent aid and later demand that their economic and social rights directly or indirectly are violated by agents of the State, by not guaranteeing security and respect for their citizenship in the space where they had a daily basis, and being exposed to a number of activities of the city to get some money that, in this context, do not guarantee the right to work set in national and international documents.